Analisis Kriminologi Kasus Pembunuhan Mahasiswa Universitas Indonesia Yang Disebabkan Oleh Pinjaman Online (Studi Kasus Pembunuhan Naufal Zidan) - Fadhlullah, Muhammad Azhar Zakiy; Valentara, Aqilla Banyu; Nugroho, Aji Bayu; Friyadhi, Naufal Farros; Rilya, Muhammad Avin Athalla; Yuli, Yuliani (Media Hukum Indonesia (MHI), 2024)
The murder case committed by a University of Indonesia student occurred on August 23 2023 and was motivated by the perpetrator getting into online loan debt due to losing playing crypto. Economic factors are one of the many factors that cause someone to commit criminal acts. Online loans have claimed many victims because debt collectors collect them in inhumane ways, causing many online loan victims to become stressed to the point of committing suicide. High interest rates and the sharing of victims' personal data are one of the dangers of online loans. In this day and age, many online loan victims commit crimes up to murder because they don't know what else to do to pay off debts with unreasonable interest rates. Here, it explains that economic factors that are unable to provide certainty for life can result in high crime rates in society. The role of government and law enforcement is needed to be able to provide economic regulations that can improve the welfare of the people and criminalise individuals or groups that cause harm to other people so that the number of crimes decreases and people can live comfortably in their environment.